How to fund clinical research in orthopedics and traumatology? Grants and opportunities - Martinez, Luis Lopez; Candido, Caio de Oliveira; Naresse, Vinicius da Silva; Lolo, Bruno Carraro; Santos, Silvonete Lima dos; Godoy-Santos, Alexandre Leme (Journal of the Foot & Ankle, 2023)
Objective: The aim of the study was to identify: how to fund clinical research in orthopedics and traumatology? Methods: A survey of funding for clinical research was performed. Results: According to data from the PIVOT® platform, the funding is concentrated in the USA, UK, and Medical Societies. The main sponsor was the DOD (USA), followed by the SICOT (Belgium). According to data from the DIMENSIONS® platform, there was a reduction of projects financed. The main country was the USA, followed by Japan. Regarding the amounts, the largest funders were the USA and Belgium. FAPESP (Brazil) is in the 7th position among sponsors. According to data from the InCites® platform, the main countries were the USA, China, and Japan. Conclusion: The reduction of projects in the last two years may be related to the limitations imposed by the SARS-CoV-2 pandemic. Regarding the amounts, the largest funders were the USA and Belgium. This data confirms the importance of funding from the SICOT. The main sponsor was the DOD; this data may be related to injuries that occurred in the war. The fact that the NIDA (USA) is the third largest funder may be related to the increase in the consumption of opioids for pain management. The incidence of falls among the elderly may be associated with Japan being one of the countries most supporting this area. Brazil is in the 8th position, and CAPES, CNPq, and FAPESP are among the top 20 funders. Level of Evidence IV; Descriptive Observational Study.